Using Multicriteria Decision Analysis to Assess Stakeholders Motivation toward Sustainable Packaging in the Fruit and Vegetable Value Chains of Rural Uganda - Kiemde, Sountongnoma Martial Anicet; Lamond, Bernard F.; Lépine, Julien (Journal of Comparative International Management, 2024)
The use of better protective packaging is often viewed as a low-cost alternative for short-run reduction of post-harvest losses in the fruit and vegetable supply chains of sub-Saharan Africa. We present the exploratory results of mapping the fruit and vegetable value chain actors in rural Uganda and analyzing their influence on the adoption of packaging. We propose a decision-aiding model based on multicriteria analysis to obtain a motivation score for assessing the degree of interest of the value chain actors toward packaging. Because it combines quantitative and qualitative information, our approach constitutes a valuable tool in the context of planning for an appropriate implementation of an appropriate packaging technology. The results suggest that distributors are the most favorable for adoption of packaging, followed by collectors, farmers, and customers, in that order. By demonstrating the use of a multicriteria decision approach for identifying the actors most likely to adopt packaging, this work suggests that the proposed approach could be used by potential regulators and manufacturers to focus their efforts on developing a well-targeted packaging deployment strategy.